Cultural Variations in Perceived Partner Responsiveness: The Role of Self-Consistency. (February 2023) - Choi, Hyewon; Oishi, Shigehiro
Past research has shown that perceived partner responsiveness (PPR) is a key process contributing to individual and relational outcomes and identified dispositional, relational, and situational factors that can influence it. However, little is known about how cultural factors play a role in the process of PPR. In Studies 1 ( n = 4, 041) and 2 ( n = 414), we examined whether the degree of PPR differs across cultures by comparing European Americans and East Asians. We found that East Asians are less likely to experience perceived responsiveness from others than European Americans (Cohen's d = 1.11–1.25 for Study 1 and Cohen's d = 0.23 for Study 2). Furthermore, we found that self-consistency explained the cultural difference in PPR, indicating that East Asians underperceived partner responsiveness compared with European Americans because they behave less consistently across social situations. We conclude by highlighting the importance of exploring the process of PPR from a cultural perspective.